Teoria Nieśmiertelności Genetycznej w relacji do Pedagogiki Holistycznej. Owoc całożyciowej medytacji = Theory of genetic immortality relatef to holistic pedagogy - Szyszko-Bohusz, Andrzej (1934- ) (Zielona Góra: Uniwersytet Zielonogórski)
Presented article consists the synthesis of the spiritual, scientific and pedagogical author's ideas.
Keywords: God; eternity; consciousness; life; love; existence; immortality; knowledge; power